2009
DOI: 10.1017/s0266467409990071
|View full text |Cite
|
Sign up to set email alerts
|

Associational resistance to a tropical leaf-miner: does neighbour identity matter?

Abstract: Associational resistance occurs when host plants experience reduced attack when in the presence of other plant species (Atsatt & O'Dowd 1976, Tahvanainen & Root 1972). The issue is most studied in agriculture and forestry because of the potential benefits to pest control (Andow 1991, Brown & Ewel 1987, Tahvanainen & Root 1972), but recent research indicates that associational resistance may be relatively common in natural systems as well (Hjältén et al. 1993, Karban 2007, Vehviläinen et al. 200… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 36 publications
2
6
0
Order By: Relevance
“…In contrast, our finding that oak vulnerability to galling and intensity of leaf mining was more severe in the presence of nearby oaks conforms to expectations of associational resistance to specialist feeders (Tahvanainen & Root, ) such as monophagous gall formers (Abrahamson, Melika, Scrafford, & Csoka, ; Hough, ) and oligophagous leaf miners (Auerbach & Simberloff, ; Faeth, Mopper, & Simberloff, ), which can feed on only one or a few related species (Castagneyrol et al, ; Himanen et al, ; Jactel & Brockerhoff, ; Lau et al, ; Orians & Björkman, ). Similarly, we found that red maples experienced a lower intensity of anthracnose infection in more phylogenetically diverse environments (Gilbert, ; Pautasso, Holdenrieder, & Stenlid, ; Peay & Bruns, ).…”
Section: Discussionsupporting
confidence: 86%
“…In contrast, our finding that oak vulnerability to galling and intensity of leaf mining was more severe in the presence of nearby oaks conforms to expectations of associational resistance to specialist feeders (Tahvanainen & Root, ) such as monophagous gall formers (Abrahamson, Melika, Scrafford, & Csoka, ; Hough, ) and oligophagous leaf miners (Auerbach & Simberloff, ; Faeth, Mopper, & Simberloff, ), which can feed on only one or a few related species (Castagneyrol et al, ; Himanen et al, ; Jactel & Brockerhoff, ; Lau et al, ; Orians & Björkman, ). Similarly, we found that red maples experienced a lower intensity of anthracnose infection in more phylogenetically diverse environments (Gilbert, ; Pautasso, Holdenrieder, & Stenlid, ; Peay & Bruns, ).…”
Section: Discussionsupporting
confidence: 86%
“…Unless other ovipositing females are present, the risk of attack to uninfested leaves is zero. Moreover, it is not uncommon for these sedentary species to aggregate (Whitham 1983;Orians and Björkman 2009). We therefore predict that damage by sedentary herbivores will favor export of resources from the attacked leaves (Fig.…”
Section: Bioticmentioning
confidence: 99%
“…Traditional neighborhood studies have often used additive or substitutive experimental designs to manipulate neighbor and focal plant densities. These designs are problematic in that they confound effects of non-focal plant density with total plant density (additive designs, [ 30 , 31 ]), or confound host plant density with non-focal density (substitutive designs, [ 32 , 33 ]), making it difficult to assess the contribution of density or relative frequency effects on damage. These confounding issues can be overcome by adopting a response surface experimental design [ 34 ] that varies the both density and relative frequency of both species independently.…”
Section: Introductionmentioning
confidence: 99%